The Effect of Locus of Control, Total Quality Management on Employee Performance with Job Satisfaction as Intervening Variable - Ramdani Bayu Putra; Ronni Andri Wijaya; Gusti Wulandari; Hasmaynelis Fitri; Yosi Yulia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
This study aims to determine the effect of Locus of Control, Total Quality Management on Employee Performance with Job Satisfaction as Intervening Variable. The object of research is the Padang UNAND Hospital. Data was obtained by distributing questionnaires to employees. Analysis Data by Path Analysis. Based on the results of this test indicate that (1) there is a positive and significant influence between Locus of Control on Job Satisfaction at Padang UNAND Hospital (2) there is a positive and significant influence between Total Quality Management on Job Satisfaction at Padang UNAND Hospital (3) there is a positive and significant influence between Locus Of Control on Employee Performance at Padang UNAND Hospital (4) There is a positive and significant influence between Total Quality Management on Employee Performance at Padang UNAND Hospital (5) There is a positive and significant influence between Job Satisfaction on Employee Performance at Padang UNAND Hospital (6) Job Satisfaction does not mediates Locus of Control on Employee Performance at Padang UNAND Hospital (7) Job Satisfaction does not mediates Total Quality Management on Employee Performance at Padang UNAND Hospital.